Features of The World Perception in Preschool-Age Children - Zakirova Muxabbat Sabirovna; Kadiyan Boobekova Sansakeevna (Next Scientists International Journal JSSHRF, 2026)
This article highlights the characteristics of preschool children's perception of the world, their acquisition of information, scientific knowledge, and social skills about their environment, and the development of their life experience. The results of studies conducted on this child are analyzed.